Ukrán szépirodalom magyar nyelven - Lebovics, Viktória (Studia Litteraria, 2024)
Hungarian translations of Ukrainian literature in Hungary and Ukraine (in Transcarpathia and, to a lesser extent, in Kiev) can be divided into three major periods. From the end of the 19th century onwards, the literary translations produced reflected the preferences of a single translator, journal or publisher, and were based on foreign translations and writings. After the Second World War, the number of Hungarian translations of Ukrainian literary works can be illustrated by a curve that started to increase slowly in the 1950s, rising relatively steeply in the 1960s and 1970s, and then gradually declining below the level of 1950s in the 1980s and 1990s. ´The output of the last thirty years or so has often included, in addition to the re-publications of previously published translations, works of well-known contemporary Ukrainian writers.